방사선학과 교육과정 개선을 위한 현 교육과정 평가 - 강세식(Se-Sik Kang); 김창수(Changsoo Kim); 최석윤(Seokyoon Choi); 고성진(Seong-Jin Ko); 김정훈(Jung-Hoon Kim) (한국콘텐츠학회 논문지, 11(5), 2011)
A curriculum of study demands a change as period of time and society evolve. Therefore, at this point where changes are required, this study is to analyze and evaluate the curriculums which will enhance and improve current studies as a preceding stage. The research was based on the survey by groups of education experts and 19 universities with current curriculum of study in radiologic science, and their references. The study was focused on the scope of work by radiologic technologist, change of college systems, academic research about radiologic science, and the improvement and the future of radiologic science field in perspective to globalization and the digital era. In terms of work scope, angiography and interventional radiology at 6 to 8 schools, fluoroscopy at 4 schools, ultrasound and practices at 6 schools, magnetic resonance image at 2 schools were found to be unestablished. The basic medical subjects, humuan physiology, human anatomy and practices, medical terminology courses were set up at most schools; however, pathology at 5 schools, image anatomy at 6 schools, clinical medicine at 11 schools were yet opened. Among the basic science and engineering subjects, general biology and its practices at 11 schools, general physics and its practices at 14 schools, and general chemistry and its practices at 8 schools were established which is about a half from a total number of schools. Only 4-5 schools established digital subjects such as, health computer, computer programming, PACS which are the basic major subjects. In order to provide academic improvement in radiologic science, digitalized education and globalization, and basis for future-oriented education for the field of radiologic science, including expanded scope of work, it is acknowledged that curriculums that are opened and run at each school need to be standardized. Therefore, the need for introduction of certificate for the radiologic science education courses are suggested. 시대와 사회적인 변화에 따라서 교육과정은 변화의 요구를 받게 된다. 교육과정의 변화를 요구받는 현시점에서 교과과정을 개선하기 위한 선행단계인 현재의 교과과정을 분석, 평가하고자 한다. 교육전문가 집단의 설문과 현재 방사선학과가 개설되어 있는 21개 대학 중 19개 대학 방사선학과의 교육과정 및 참고문헌을 중심으로 연구하였으며, 연구내용은 방사선사 업무범위와 교과과정, 방사선과학 교육과 교과과정, 디지털과 국제화시대의 교과과정, 방사선과학에 대한 학문적인 발전과 교과과정 등의 내용을 중심으로 연구하였다. 업무범위에서는 혈관조영학 및 중재적검사학은 6 ~ 8개교, 투시영상학은 4개교, 초음파영상학 및 실습은 6개교, 자기공명영상학은 2개교 등에서 미개설된 것으로 나타났다. 기초의학 교과목인 인체생리학, 인체해부학 및 실습, 의학용어 등은 대부분의 대학에서 개설되어 있었으나, 병리학 5개교, 영상해부학 6개교, 임상의학 11개교 등에서 미개설 되어 있는 것으로 나타났다. 기초이공학 교과목 중에서 일반생물학 및 실습은 11개교, 일반물리학 및 실습은 14개교, 일반화학 및 실습은 8개교 등 약 절반정도의 대학에서 개설된 것으로 나타났다. 전공기초에서 디지털화 교과목인 보건전산학, 컴퓨터프로그램밍, PACS 등이 개설된 대학은 4 ~ 5개교에 불과하였다. 방사선과학 교육은 확대된 업무범위를 포함하여, 방사선과학의 학문적 발전과 디지털화 교육 및 국제화 그리고 방사선과학 분야의 미래지향적인 교육의 토대를 마련하기 위해서는 현재 각 대학에서 개설, 운영되고 있는 교과과정은 일정부분 표준화의 필요성을 인식하였으며, 이에 방사선학과 교육과정은 인증제 도입의 필요성을 제시한다.